Liderazgo pedagógico del directivo en el desempeño docente de la Institución Educativa N° 60160 del distrito de Fernando Lores 2021 - Solano Sanchez, Iris (2023)
The objective of this research was to explain the influence of the director's pedagogical leadership on the teaching performance of Educational Institution No. 60160 in the Fernando Lores district during the 2021 school year. The study allowed us to reach the conclusion that there is no influence of pedagogical leadership of the director in the teaching performance of Educational Institution No. 60160 of the Fernando Lores district during the 2021 school year. Regarding the general hypothesis, the null hypothesis is accepted because after the inferential statistical analysis it shows that there is no significant correlation between pedagogical leadership of the manager in the teaching performance of the Educational Institution No. 60160, the Spearman Rho Correlation test has been taken into account for the variables of managerial pedagogical leadership and teaching performance with a coefficient of -0.128 and a significance of 0.677, at a sample of 52 teachers.